2012
DOI: 10.1186/1471-2458-12-842
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and socioeconomic influences of tobacco exposure in tobacco cultivating rural areas of Yunnan Province, China

Abstract: BackgroundThis study describes the patterns and socioeconomic influences of tobacco use among adults in tobacco-cultivating regions of rural southwest China.MethodsA cross-sectional survey was conducted in 8681 adults aged ≥18 years in rural areas of Yunnan Province, China from 2010 to 2011. A standardized questionnaire was administered to obtain data about participants’ demographic characteristics, individual socioeconomic status, ethnicity, self-reported smoking habits, and exposure to secondhand smoke (SHS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 23 publications
20
31
0
1
Order By: Relevance
“…This stands in contrast to the findings of some other studies. In a study of adults living in rural areas in Yunnan Province Cai et al (2012Cai et al ( , 2013 found that individuals who cultivated tobacco smoked more than those that did not. Similarly, Hoffer and Pellilo (2012), while they did not directly examine the direct effects of tobacco cultivation on smoking, nevertheless found the former to be important factor influencing tobacco control expenditures.…”
Section: Discussionmentioning
confidence: 97%
“…This stands in contrast to the findings of some other studies. In a study of adults living in rural areas in Yunnan Province Cai et al (2012Cai et al ( , 2013 found that individuals who cultivated tobacco smoked more than those that did not. Similarly, Hoffer and Pellilo (2012), while they did not directly examine the direct effects of tobacco cultivation on smoking, nevertheless found the former to be important factor influencing tobacco control expenditures.…”
Section: Discussionmentioning
confidence: 97%
“…However, China has very few estimates of tobacco's costs, and past studies have been to focus on the estimation of economic burden associated with smoking-related diseases [5,9], while overlooking the economic costs of SHS exposure, especially in rural areas. Seventy percent of China's population lives in the countryside, and rural residents have higher prevalence rate of smoking and SHS exposure than urban inhabitants [3,10]. Based on past research conducted both inside and outside China, smoking has been demonstrated to be important contributors to COPD, asthma, coronary heart disease (CHD), stroke, hypertension and peptic ulcer [1,2,5,[11][12][13][14], which indicated that smoking increased the risk of overall mortality, accounting for more deaths than any other single cause.…”
Section: Introductionmentioning
confidence: 99%
“…A link has also been observed between smoking and socioeconomic status (SES), with persons from low socioeconomic backgrounds more likely to be smokers in Western countries, including Australia,17–21 the UK18 20 22 and the USA,18 20 22 23 although this relationship may not generalise to less developed countries 24 25. The exact mechanisms behind socioeconomic difference in smoking are unknown, but have been linked to impoverished environments and lack of access to positive activities and alternatives to drugs 26.…”
Section: Introductionmentioning
confidence: 99%